Grey theory based evaluation of importersâ€™ strategies for hedging the price risk in the Tanzanian oil supply chain: a focus on derivative products - P. Massami, Erick; M. Manyas, Malima; M. Myamba, Benitha (International Journal of Applied Mathematical Research, 2018)
The landed cost for oil products in local markets is very often affected by the fluctuation of price related to the international purchasing from oil markets. As a result, oil products are primarily procured via term contracts i.e. derivatives as wholesalers are typically loath to rely heavily on spot supplies as these may be unreliable and exhibit high price volatility. In this study, we apply Grey Theory to evaluate the derivatives based strategies of the Tanzanian oil products imports for hedging the price risk in the local market. After comprehensive evaluation, we find that the applicability of oil derivatives by the Tanzanian importers is high. Thus, the government (i.e. Ministry of Finance and Planning, Ministry of Trade and Industry) and other stakeholders have the obligation to continue bringing awareness on the benefits of the derivative instruments in the purchasing of oil products, which ultimately upon application would bring a relief to all consumers of the oil products in the country. Moreover, as the grey theory can deal with vague and incomplete data, the proposed model can be applied as an evaluation tool for quantifying qualitative data in any industry.Â Â